Back to work: The making and unmaking of the English working class. Issue 1 (7th June 2013) - Lawrence, Jon
Abstract : On its 50th anniversary, Jon Lawrence looks back at EP Tompson's classic The Making of the English Working Class and asks what potential there is today for a 'new politics for working people' that doesn't fall into the trap of trying to remake working‐class politics.